ALKALOIDS ISOLATED FROM PLANTS AND THEIR PHARMACEUTICAL APPLICATIONS (Modern American Journal of Medical and Health Sciences, 2025)
This article provides a comprehensive overview of the chemical structure, extraction methods, biological activity, and pharmaceutical applications of alkaloids derived from plants. Alkaloids are natural nitrogen-containing organic compounds that serve as the basis for numerous medicinal drugs. Notable alkaloids such as morphine, atropine, caffeine, nicotine, and reserpine are widely used in modern medicine as analgesics, sedatives, antispasmodics, and other therapeutic agents. The article discusses technologies for isolating alkaloids from plant materials, their chemical synthesis, biological effects, and emerging trends in pharmaceutical usage. Additionally, it addresses the side effects of alkaloids and strategies to minimize them. These studies contribute to a deeper understanding of the significance of plant-derived alkaloids in pharmaceuticals and expand opportunities for their effective use as medicinal agents.